Generalization of the Faraday problem for the mechanical system «reservoir – liquid» in the presence of a vertical periodic (sawtooth) disturbance - Константінов, Олександр; Семенович, Катерина (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2024)
The generalization of Faraday’s classic problem about the parametric resonance of the free surface during vertical oscillations of the tank according to the periodic law of the modulus of the cosine is considered. Regions of stability and instability are designed, which are compared with similar results for the classical Faraday problem. The behavior of the system is considered on the basis of a nonlinear multimode model, which describes the combined movement of the tank and fluid under the influence of external force excitation or kinematic disturbance. It is shown,the oscillations of the free surface liquid in both cases of Faraday problem are qualitatively similar, and therefore any of the selected types of disturbances can be used in research on parametric resonance to obtain a qualitative effecton the oscillations of the free surface liquid.